2019
DOI: 10.1029/2019gl086274
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Decay of Slowly Moving Typhoon Soulik (2018) due to Interactions With the Strongly Stratified Northern East China Sea

Abstract: Typhoon Soulik decayed rapidly via two-way interaction with the northern East China Sea, the extratropical shelf region, before landing on the Korean Peninsula on 23 August 2018. In the northern East China Sea, where the water column is strongly stratified with warm surface and cold subsurface waters, a large cold wake emerged with intense sea surface cooling, which is primarily caused by vertical mixing in the water column. This abrupt sea surface cooling rapidly increased the downward enthalpy flux, mostly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…These constraints can influence the way sea surface temperature (SST), the critical thermodynamic interface for ocean–storm interaction, evolves and thus modifies storm intensity 9 . Several studies have shown that the presence of stratification prior to storm arrival can significantly reduce the intensity of impending storms, via ahead-of-eye SST cooling 7 , 8 , 10 , 11 . Conversely, other studies have suggested or shown that anomalously warm conditions on shelves have contributed to the intensification of hurricanes through landfall 6 , 12 14 .…”
Section: Introductionmentioning
confidence: 99%
“…These constraints can influence the way sea surface temperature (SST), the critical thermodynamic interface for ocean–storm interaction, evolves and thus modifies storm intensity 9 . Several studies have shown that the presence of stratification prior to storm arrival can significantly reduce the intensity of impending storms, via ahead-of-eye SST cooling 7 , 8 , 10 , 11 . Conversely, other studies have suggested or shown that anomalously warm conditions on shelves have contributed to the intensification of hurricanes through landfall 6 , 12 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (2,4,39) have emphasized the need to use coupled mesoscaleresolving global atmosphere/ocean models in projecting the sensitivity of TCs to future climate change. Our results which are based on one of the highest-resolution coupled global model simulations of long-term future climate change conducted so far, provide new insights into the robustness of previously identified mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…TCs are detected and tracked by adopting (with some minor adjustments) a recently proposed method 4 . For our detection we use 6-hourly instantaneous surface pressure, 10-m wind speed, and surface vorticity.…”
Section: Tc Detection and Trackmentioning
confidence: 99%
See 1 more Smart Citation
“…By 22 August, the intensity of Soulik had reached a stage of "very strong (wind speed of 44-54 m/s)", according to the typhoon intensity criteria of KMA, with a central pressure of 950 hPa and maximum wind speed of 43 m s −1 . Soulik weakened rapidly after the maximum stage, with the maximum wind speed decreasing to 12 m s −1 within 30 h [28]. Typhoon Francisco began to develop on 2 August 2019, over the ocean~1120 km northeast of Guam.…”
Section: Typhoonsmentioning
confidence: 99%